Pengelolaan Penerimaan Peserta Didik Baru Melalui Sistem Online Di Sma Negeri 1 Karanganom Klaten - Bawana, Guntur, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum, Dr. Wafrotur Rohmah, M.M (2016)
Guntur Bawana. Q 100 140 024. Management of New Students Admission by Online System at SMA Negeri 1 Karanganom Klaten. Thesis. Educational Administration Program. Postgraduate School of Muhammadiyah University of Surakarta. 2016. The objectives of research are: (1) to describe preparation of new students admission by online system at SMA Negeri 1 Karanganom Klaten. (2) to describe organization of new students admission by online system at SMA Negeri 1 Karanganom Klaten. (3) to describe implementation of new students admission by online system at SMA Negeri 1 Karanganom Klaten. This research uses qualitative method, with ethnography study design. Data is collected by in depth interview, document analysis, and observation. Data validity use source and method triangulation. Data analysis in this research use Interactive Model of Analysis. The results of research about management of new students admission by online system at SMA Negeri 1 Karanganom Klaten are: (1) Preparation done towards of new students admission, involves technical and implementation guidelines forming, socialization, and preparations of computer facilities and internet network. (2) Organizing of new students admission involves formation and coordination meeting of committee, computer and internet operators training. (3) Implementation of new students admission by online system is still half offline because it still has manually form data filling and entry data by school, there is simplicity of registrations process, there is no charge for registration and transparency. Difficulties of this system are there is matter of repeal in registration files without regional education authority's recommendation. Keywords: management; new students admission; online system